Gastrointestinal parasitism in goats and role of seasonal changes on their prevalence: A study of Nepal - Rajesh Kumar Das; Prabin Neupane; Endang Sulistyowati (AGRITROPICA : Journal of Agricultural Sciences, 2019)
Goat farming is the good source of income for people living in countryside, Nepal. This occupation supports socioeconomic living of many people in developing countries. Gastro-parasitic infections in goats can decrease the meat supply in a country where demand of goat meat is ever increasing. The objective of this study was to identify the gastrointestinal parasites in feces of goats and impact of seasonal changes on their prevalence. This is a cross-sectional study done on 212 goats from Kapilbastu, Nepal. For this study, feces of goats were collected during summer and winter and observed microscopically to find the causative organisms. The result showed the helminths from trematode (22.22%), cestode (12.5%) and nematode (65.27%) caused heavy gastrointestinal infection in 144 microscopically positive samples taken from Kapilbastu, Nepal. The major helminths were Toxocara (16.66%), Oesophagnum (8.32%), Strongyloides (6.25%) and Trichuris (4.86%) among nematodes, Fasciola  (15.97%) caused highest infection among trematode and Taenia (9.72%) among cestode. The prevalence of these infections was significantly higher during summer than winter. The higher prevalence of these helminths is the indication of supply contaminated food and water. Moreover, unawareness and ignorance about such diseases can increase the infection rate. Proper management of goat farm together with good cattle rearing training can increase the productivity.